Knowledge networking : creating the collaborative enterprise - Skyrme, David J.; ScienceDirect eBooks (Oxford ; Boston : Butterworth-Heinemann, 1999)
Knowledge Networking explains the strategic, organizational and human impact of technologies that support knowledge: the internet, groupware, collaborative technologies. It shows how they can transform organizational practices and help to improve both individual and team performances. Based on proven experience and includes customised toolkits, cases and action plans. From pooling expertise on a sales bid via computer referencing, to improving customer service using the flexible office, the author demonstrates how potential can become practice. Knowledge management is the big management idea currently influencing organizations, and Knowledge Networking explores the global impact of sharing knowledge and expertise. It is a highly practical text which includes customised toolkits, cases and action plans to enable individuals and teams to improve their performance. Shows how collaboration and teamworking can be enhanced through knowledge networking Concerned with people, processes and practicalities not theory and technology Includes access to the author's internet newsletter on knowledge management.
Features of the knowledge economy; The enabling technologies; Exemplars and cases; Strategies for success; Index.
Includes bibliographical references (pages 288-293) and index.
Print version record.
Safari Books Online
Elsevier
Keywords: Business information services; Commerce -- Information services; Business enterprises -- Computer networks; Business planning; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Business enterprises -- Computer networks; Business information services; Business planning; Commerce -- Information services; Kennismanagement; Electronic books